Formación ciudadana : ¡utopía posible! (2009)
ABSTRACT: Citizenship education is not just an aspiration, it is a need to build and consolidate the Latin-American democratic project. This democracy requires renewed citizens, it is, democratic, participative, social, political, active, and critical citizens, willing to practice a new citizenship, beyond the classic one. That is why territorial studies, from the teaching point of view, become an opportunity to educate in, for and on citizenship, a task that includes instruction, development, and education in context. Education for citizenship must be intended to and guided from the theory of conscious processes, in order to promote territorial citizens, able to practice their citizenship and willing to build territorial democracy.